2003
DOI: 10.1002/ceat.200303008
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Measurement of the Dissolution Rate of Solid Particles in Aqueous Suspensions – Part II: Experimental Results and Validation

Abstract: The dissolution rate of limestone was measured by the pH‐stat method. In the measurements the influence of pH, particle size, kind of limestone, sparging and stirrer speed was first examined for particle fractions with narrow size distributions. Under the assumption that each particle size distribution is adequately represented by its mean particle size, the monodisperse model presented in Part I was adjusted to these data. The adjusted model was combined with the population balance and the three‐phase model d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Toprac and Rochelle [1] found that there is no effect of limestone type and particle size distribution is the most important influence factor of limestone dissolution. Chan and Rochelle [2], Wallin and Bjerle [3] and Allers et al [4,5] studied the dissolution rate of limestone in a pH-stat apparatus under various conditions and reported that the dissolution process can be successfully simulated by mass transfer model combined with the effects of several equilibrium acid/base reactions and the finite reaction of CO 2 and H 2 O in the boundary layer. Other researchers found that surface reaction may also affect the dissolution process of limestone.…”
Section: Introductionmentioning
confidence: 99%
“…Toprac and Rochelle [1] found that there is no effect of limestone type and particle size distribution is the most important influence factor of limestone dissolution. Chan and Rochelle [2], Wallin and Bjerle [3] and Allers et al [4,5] studied the dissolution rate of limestone in a pH-stat apparatus under various conditions and reported that the dissolution process can be successfully simulated by mass transfer model combined with the effects of several equilibrium acid/base reactions and the finite reaction of CO 2 and H 2 O in the boundary layer. Other researchers found that surface reaction may also affect the dissolution process of limestone.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, whilst heterogeneous systems are widely used in the production of fine chemicals, there is little literature information on the dissolution of solid particles in organic solvents. Formerly, studies of the dissolutions of inorganic solids have been in aqueous solutions, [7][8][9][10][11] such as the dissolution of limestone in aqueous electrolyte, 10,[12][13][14][15] and only particles of sizes in a small diameter fraction or single crystals have been selected.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating Equations (19), (20) and (21) and imposing the boundary conditions at the solid-liquid interface, r = r j , (Equations (26) and (28)), applying Fick's First Law in the radial direction, we obtain:…”
Section: Boundary Conditionsmentioning
confidence: 99%